1986
DOI: 10.1111/j.1365-2621.1986.tb13851.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potency of Plant Antinutrients towards the In Vitro Digestibility of Buckwheat Protein

Abstract: The inhibitory potency of dietary fiber sources, tannins, phytate, and a protein protease inhibitor on the in vitro pepsin-pancreatin digestibility of protein was compared. The protein inhibitor exhibited the highest inhibitory capacity among the substances examined; and phytate the lowest. Our findings suggest that the inhibition of the digestion of dietary sources of plant proteins by such factors as fiber and tannins, in addition to the protein protease inhibitors, may also be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
2
25
0
2
Order By: Relevance
“…Indeed buckwheat protein appears to be less readily utilised than wheat protein, and dietary fibre may play role. However, high intake of dietary fibre is not likely to be problematic when protein and minerals in the diet are adequate (Ikeda, Oku, Kusano, & Yasumoto, 1986;Roberfroid, 1993). Bonafaccia et al (2003a) in study of elemental composition of the main utilisable grain fractions of tartary and common buckwheat have reported that the bran fraction has a higher content of Se, Zn, Co, Ni, Rb and Sb than flour (see Table 1).…”
Section: Main Nutritional Componentsmentioning
confidence: 97%
“…Indeed buckwheat protein appears to be less readily utilised than wheat protein, and dietary fibre may play role. However, high intake of dietary fibre is not likely to be problematic when protein and minerals in the diet are adequate (Ikeda, Oku, Kusano, & Yasumoto, 1986;Roberfroid, 1993). Bonafaccia et al (2003a) in study of elemental composition of the main utilisable grain fractions of tartary and common buckwheat have reported that the bran fraction has a higher content of Se, Zn, Co, Ni, Rb and Sb than flour (see Table 1).…”
Section: Main Nutritional Componentsmentioning
confidence: 97%
“…Important part of buckwheat proteins are resistant to digestion or are slowly digested (K. Ikeda et al 1986Ikeda et al , 1991. Authors report about low digestibility rate of buckwheat proteins because of the presence of enzyme inhibitors including protease inhibitors (K. Ikeda & Kishida 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Of special importance are essential amino acids, like lysine (Eggum 1980, Javornik 1983, K. Ikeda et al 1991 and rich selection of elements (S. Ikeda & Yamashita 1994.…”
Section: Discussionmentioning
confidence: 99%
“…These are probably connected with the limited digestibility of buckwheat proteins [3,14,15]. The high content of proteins in certain buckwheat grain milling fractions suggests a potential application of these materials for special dietary products [16].…”
Section: Introductionmentioning
confidence: 99%